All-solid-state thin-film batteries based on lithium phosphorus oxynitrides. (23rd September 2022) - Dai, Wangqi; Qiao, Yan; Ma, Ziqiang; Wang, Tian; Fu, Zhengwen
Abstract: Lithium phosphorus oxygen nitrogen (LiPON) as solid electrolyte discovered by Bates et al in the 1990s is an important part of all-solid-state thin-film battery (ASSTFB) due to its wide electrochemical stability window and negligible low electronic conductivity. However, the ionic conductivity of LiPON about 2 × 10 −6 S cm −1 at room temperature is much lower than that of other types of solid electrolytes, which seriously limits the application of ASSTFBs. This review summarizes the research and progress in ASSTFBs based on LiPON, in the solid-state electrolyte of LiPON-derivatives with adjustable chemical compositions of the amorphous structure for the improvement of the ionic conductivity and electrochemical stability, in the critical interface issues between LiPON and electrodes, and in preparation methods for LiPON. This review is helpful for people to understand the interface characteristics and various preparation methods of LiPON in ASSTFBs. The key issues to be addressed concern how to develop solid-state electrolyte films with high conductivity and high-quality interface engineering as well as large-scale preparation technology, so as to realize the practical application of highly integrated ASSTFBs.